The Tungkot Tunggal Panaluan Batak Statue As A Source Of Inspiration For The Creation Of Painting Artworks - Manalu, Joel; Tarigan, Nelson (Institut Seni Indonesia Padang Panjang, 2023)
The author's fascination inspired the creation of this work with the Tungkot Tunggal Panaluan Batak statue, a significant element of Batak culture, notable for its shape, history, and function. This statue portrays seven individuals supporting each other, diminishing in size, set against diverse backgrounds. The research seeks to visualize the form, history, and applicability of the Tungkot Tunggal Panaluan statue from the distant past to the present day, manifesting as paintings accompanied by descriptions of their meanings and the techniques employed in their creation. The author produced 12 paintings in this study using acrylic and oil paints on canvas. These artworks feature human figures and primitive Batak figurative statues, characterized by stylized forms, set against a simple village backdrop that serves as a historical context for Tungkot Tunggal Panaluan. Historically, this statue was employed by leaders in traditional Batak community events. The author combined three techniques—plaque, chiaroscuro, and bravura—to infuse the paintings with dynamic impressions, contrasts, and vitality. Notably, the chiaroscuro technique was employed to balance dark and light, utilizing paint colors derived from raw umber and yellow ocher combined with primary colors to evoke a vintage atmosphere. The outcomes of this research comprise 12 paintings, each titled uniquely, reflecting the author's interpretation of the Tungkot Tunggal Panaluan statue in the realm of fine art. These works offer a profound insight into the statue's form, history, and function, contributing significantly to the author's impact on the evolution of painting.